Pengaruh Sistem Informasi Akuntansi Manajemen, Sistem Pengukuran Kinerja Dan Sistem Penghargaan Terhadap Kinerja Manajerial Pada Pt. Kawasan Industri Medan - Leni Deli; Irfan Irfan (Jurnal Riset AKuntansi dan Bisnis, 2026)
This study aims to examine and analyze the influence of management accounting information systems, performance measurement systems, and reward systems on managerial performance at PT Kawasan Industri Medan. The sampling technique employed is the saturated sampling method, resulting in a total sample size of 32. Data collection was conducted via questionnaires distributed to managers, assistant managers, and supervisors at PT Kawasan Industri Medan (PT KIM). Data analysis involved outer model analysis, inner model analysis, and hypothesis testing using Partial Least Squares (PLS) software. The results indicate that: 1) the management accounting information system has a significant effect on managerial performance; 2) the performance measurement system does not have a significant effect on managerial performance; and 3) the reward system does not have a significant effect on managerial performance.